Antimicrobial and fungicide activity of anthraquinones from Aloe vera L. combined with copper, iron, silver and bismuth cations - Saavedra, Félix E. (2012)
This study aimed to evaluate the antimicrobial and fungicidal activity of aqueous and alcoholic macerated from leaves of Aloe vera L., containing anthraquinone derivatives. With this macerated liquids were prepared solutions of CuSO4.5H2O 1,5%, FeCl3 1%, AgNO3 1%, and Bi (NO3)3 1,5%, which were stored in amber glass flasks, hermetically closed for 12 months under refrigeration; a similar batch was kept at 25°C. Antimicrobial and fungicide activities were determined on these preparations using plate excavation method, of USP XXX, against Staphylococcus aureus, Pseudomonas aeruginosa, Escherichia coli and Aspergillus niger strains. Aqueous solutions of Aloe vera L. showed antimicrobial activity in decreasing order Cu > Ag > Fe and alcoholic solutions in also decreasing order Ag > Cu > Fe. Only copper sulphate aqueous solutions showed fungicidal activity. The preparations preserved under refrigeration, had greater antimicrobial and fungicidal activity than equivalent preparations preserved at room temperature of 25°C.